2008
DOI: 10.1074/jbc.m803047200
|View full text |Cite
|
Sign up to set email alerts
|

The Thermodynamics and Kinetics of Electron Transfer between Cytochrome b6f and Photosystem I in the Chlorophyll d-dominated Cyanobacterium, Acaryochloris marina

Abstract: We have investigated the photosynthetic properties of Acaryochloris marina, a cyanobacterium distinguished by having a high level of chlorophyll d, which has its absorption bands shifted to the red when compared with chlorophyll a. Despite this unusual pigment content, the overall rate and thermodynamics of the photosynthetic electron flow are similar to those of chlorophyll a-containing species. The midpoint potential of both cytochrome f and the primary electron donor of photosystem I (P 740 ) were found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 59 publications
5
22
1
Order By: Relevance
“…To assess the existence of restricted diffusion domains, we compared the theoretical equilibrium constant ( K th ) between PSI and its electron donors (cyt) with the experimental one ( K exp ), following previous approaches in plants3 and bacteria38. In P. tricornutum we calculate a value of 16 for K th , based on the redox potentials of cyt c 6 (349 mV)16 and of P 700 (420 mV)17.…”
Section: Methodsmentioning
confidence: 99%
“…To assess the existence of restricted diffusion domains, we compared the theoretical equilibrium constant ( K th ) between PSI and its electron donors (cyt) with the experimental one ( K exp ), following previous approaches in plants3 and bacteria38. In P. tricornutum we calculate a value of 16 for K th , based on the redox potentials of cyt c 6 (349 mV)16 and of P 700 (420 mV)17.…”
Section: Methodsmentioning
confidence: 99%
“…Initially it was discovered that the redox mid-point potential ( E m ) of P 740 is 335 mV, which is 120–150 mV more negative than P 700 , which has E m  = +420 to +450 mV [2]. However later on it was found that A. marina P 740 of PSI has same redox potential like P 700 of normal PSI [36, 37]. Due to the presence of Chl d , it can absorb energy at longer wavelength than P 700 .…”
Section: Photosystem Imentioning
confidence: 99%
“…The midpoint potential for cytochrome f and the primary electron donor of PSI (P 740 ) were discovered to be unaltered as compare to other photosynthetic species having Chl a and it was 345 mV for Cyt- f and 425 mV for P 740 . These results revealed that the midpoint potential of the special pair is not adjusted to the incoming flux of weak excitionic energy in this organism and to conserve the reducing power of PSI [37]. Further investigations revealed that there is no hindrance in the circulation of soluble electron transport protein between cytochrome- b6f and PSI in A. marina .…”
Section: Photosystem Imentioning
confidence: 99%
See 2 more Smart Citations